Chitosan-coated niosome as an efficient curcumin carrier to cross the blood–brain barrier: an animal study. (3rd July 2022) - Salehi, Sahar; Nourbakhsh, Mohammad Sadegh; Yousefpour, Mardali; Rajabzadeh, Ghadir; Sahab-Negah, Sajad
Abstract: This study aims to improve the curcumin bio-stability and brain permeability by loading in bare niosome (BN) and chitosan-coated niosome (ChN). Span 60, tween 60, and cholesterol were optimized as niosome shell components to attain the highest encapsulation efficiency (EE), besides the lowest particle size, using the mixture design method. The resulting optimized BN had a mean diameter of 80 ± 0.2 nm and surface charge of −31 ± 0.1 mv, which changed to 85 ± 0.15 nm and 35 ± 0.12 mv, respectively, after applying the chitosan layer. The EE% in bare niosome were about 80 ± 0.2, which changed to 82 ± 0.21 in ChN. The optimized formulation displayed sustained release, following the Hixson–Crowell model. Wistar rats were subjected to intraperitoneal injection (i.p.) of BN and ChN to evaluate the blood-brain barrier permeability of the curcumin. In this regard, ChN significantly increased curcumin concentration in different parts of the liver, plasma, and central nervous system (cerebral cortex, cerebellum, and stratum), compared with BN. Altogether, our results showed that ChN could be used as a promising delivery system for the treatment of some neurological diseases such as Alzheimer ' s.